If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = -6c + -4 Reorder the terms: 12 = -4 + -6c Solving 12 = -4 + -6c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '6c' to each side of the equation. 12 + 6c = -4 + -6c + 6c Combine like terms: -6c + 6c = 0 12 + 6c = -4 + 0 12 + 6c = -4 Add '-12' to each side of the equation. 12 + -12 + 6c = -4 + -12 Combine like terms: 12 + -12 = 0 0 + 6c = -4 + -12 6c = -4 + -12 Combine like terms: -4 + -12 = -16 6c = -16 Divide each side by '6'. c = -2.666666667 Simplifying c = -2.666666667
| 3x-27/3x= | | -32,424/-84 | | 2x-5(x-5)=-3+4x+14 | | -(x)(x+0)(x-5)=0 | | 4+2=5x+1 | | 5(m-3)=24 | | (x-5)(x+0)(x+7)=0 | | X/Y=-4/5 | | (15/10)^(1/4)-1 | | 8x+1=31 | | (b+16)(b-18)=0 | | 9-4(2x-1)-3x+2= | | 3x^4-21x^3+24x^2+23x-34=0 | | 20(7u-8v+3w)= | | 7z+2=-6 | | -7+2=6 | | 9x+16-6x=10-2x-19 | | 2p-3=p-5 | | 5a-16=25 | | v^2-10v+16= | | 4w-3x-y-5w+18x-7y= | | -6+[25+(-12)]=43 | | X^2+100+60-3x+30-4x=180 | | -6+[25+(-12)]=31 | | -13+2x=-52+13 | | -6+[25+(-12)]=7 | | -6+[25+(-12)]=19 | | 4=5+2x | | 5x+17-4x=-2-10 | | X/Y=7/11 | | 3x^2-(3m-2)x-(3m+1)=0 | | 1/3*1/3*1/3*1/3*a*a*b*b*c |